2014
DOI: 10.1186/1756-0500-7-189
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the two-component sensor protein CiaH to acid and oxidative stress responses in Streptococcus pyogenes

Abstract: BackgroundThe production of virulence proteins depends on environmental factors, and two-component regulatory systems are involved in sensing these factors. We previously established knockout strains in all suspected two-component regulatory sensor proteins of the emm1 clinical strain of S. pyogenes and examined their relevance to acid stimuli in a natural atmosphere. In the present study, their relevance to acid stimuli was re-examined in an atmosphere containing 5% CO2.ResultsThe spy1236 (which is identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Similarly, the stress response genes ciaHR, nrdR, and spxA2 and the arginine deiminase pathway genes arcABCD had significantly increased transcript levels in the ΔrocA M28 mutant strain ( Fig. 4) (44,48,61,74,75). Consistent with the RNA-seq data, the isogenic ΔrocA strain had increased resistance to acidic stress, a condition encountered in purulent lesions (70)(71)(72).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similarly, the stress response genes ciaHR, nrdR, and spxA2 and the arginine deiminase pathway genes arcABCD had significantly increased transcript levels in the ΔrocA M28 mutant strain ( Fig. 4) (44,48,61,74,75). Consistent with the RNA-seq data, the isogenic ΔrocA strain had increased resistance to acidic stress, a condition encountered in purulent lesions (70)(71)(72).…”
Section: Discussionsupporting
confidence: 58%
“…During infection, GAS cells are exposed to oxidative and acid stress in purulent lesions (70)(71)(72). Among the 41 transcription regulators that are directly or indirectly regulated by RocA in M28 GAS, 4 are implicated in oxidative and acidic stress responses, including the CiaHR twocomponent system, NrdR, and SpxA2 (Table 1) (44,48,61). Additionally, the arcABCD operon had significantly increased transcript levels in the ΔrocA mutant strain ( Fig.…”
Section: Roca Directly or Indirectly Regulates Transcription Regulatomentioning
confidence: 99%
“…ciaH has been reported to be involved in GAS responses to acid and oxidative stresses (80). Interestingly, a previous virulence study found that the ciaH deletion mutant was not attenuated in a mouse model of infection, but the route of inoculation was not specified (80). We used the mouse model of necrotizing myositis to test the hypothesis that deletion of ciaH significantly decreases virulence.…”
Section: Contribution Of Five New Genes To Necrotizing Myositis Virulmentioning
confidence: 99%
“…The ciaH gene encodes the histidine kinase sensor protein of the CiaHR regulator two-component system (TCS). ciaH has been reported to be involved in GAS responses to acid and oxidative stresses (80). Interestingly, a previous virulence study found that the ciaH deletion mutant was not attenuated in a mouse model of infection, but the route of inoculation was not specified (80).…”
Section: Contribution Of Five New Genes To Necrotizing Myositis Virulmentioning
confidence: 99%
“…ciaH , an another important TCS which controls about 120 genes [ 21 ] and involved in oxidative stress and acid tolerance [ 51 ] was found to be down regulated. An earlier report which demonstrated the increased aggregation pattern in srtB mutant M6 strain [ 52 ] aroused great interest in us to study the gene expression pattern of spy_125/srtB gene in SF370 which was found to be down regulated.…”
Section: Discussionmentioning
confidence: 99%